2022
DOI: 10.1021/acs.jpcc.2c02258
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Effects of the Photophysics of Rhodamine 6G Ultra-Thin Films on a Poly(methylmethacrylate) Surface

Abstract: The absorbance, excitation, and emission spectra of ultra-thin films of rhodamine 6G (Rh6G) spin-cast on poly(methylmethacrylate) (PMMA)-coated glass slides are examined as a function of both PMMA and Rh6G thickness. The thickness of PMMA has a little effect on the absorption or emission properties of Rh6G. At low surface coverage, the spectral properties of Rh6G are dominated by isolated molecules. As the Rh6G thickness increases, there is no evidence for exciton formation. Instead, the Rh6G molecules aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The changes of the optical properties of rhodamine dyes at interfaces have been studied for many years. ,, Depending on the nature of the substrate, the studies have shown that rhodamines can readily aggregate, ,, can have direct ion-π interactions with the substrate, or the aggregation can be suppressed. , Whether this is due to the properties of the dyes or the substrates is not fully resolved, but probably is a combination of both.…”
Section: Introductionmentioning
confidence: 99%
“…The changes of the optical properties of rhodamine dyes at interfaces have been studied for many years. ,, Depending on the nature of the substrate, the studies have shown that rhodamines can readily aggregate, ,, can have direct ion-π interactions with the substrate, or the aggregation can be suppressed. , Whether this is due to the properties of the dyes or the substrates is not fully resolved, but probably is a combination of both.…”
Section: Introductionmentioning
confidence: 99%